KOMPOSISI GUILD KOMUNITAS BURUNG DI AREA PANAS BUMI CAGAR ALAM DAN TAMAN WISATA ALAMKAMOJANG JAWA BARAT INDONESIA - Diyah Kartikasari; Satyawan Pudyatmoko; Novianto Bambang Wawandono; Pri Utami (Lambung Mangkurat University-Indonesia, 2018)
This study aims to investigate the response of Bird Communities Guild Composition in Geothermal Area Kamojang Nature Reserve and Kamojang Nature Park West Java Indonesia. We compared the number of species, the number of individuals and the composition of bird guilds of directly affected (DL) and not affected (TL) in Kamojang geothermal working area, Kamojang nature reserve and Kamojang nature park in Bandung regency of West Java Province. The directly affected sites were surrounding production wells or geothermal power plants (30 samples) whereas indirectly affected sites were with distance of 3,000 m to 9,000 m from those facilities (42 samples). The data collection was carried out during two seasons; dry and rainy season in (2015-2016). We collected bird community data with the point count method which was placed systematically on each site. We found 124 bird species in CA / TWA Kamojang and 90 species (1560 individuals) of birds at the sample point. The number of species and the number of individual in TL locations is greater than the DL (DL locations = 65 species, 525 individuals; TL sites = 72 species, 1035 individuals). There is a difference of responses between bird communities in the DL and TL sites which is indicated by differences in the mean number of species and number of individuals in each point count.The mean number of species and the number of individual birds per point count in the TL location is greater than DL.The CA / TWA area of Kamojang has seven bird guilds: insectivores, frugivores, granivores, nectarivores, carnivores, piscivores and omnivores. The results of the significance test on the number of species and the number of individuals per guild showed no significant differences between the DL and TL sites, but the birds in DL were commonly found (generalists) and birds found in TL sites were mostly specialist. This proves that the TL location has better environmental conditions or relatively undisturbed.Penelitian ini bertujuan untuk menguji komposisi guild komunitas burung di Area Panas Bumi Cagar Alam dan Taman Wisata Alam Kamojang. Penulis membandingkan jumlah jenis, jumlah individu dan komposisi guild burung pada lokasi yang terdampak langsung (DL) dan tidak terdampak langsung (TL) di Wilayah Kerja Panas Bumi Kamojang, Cagar Alam Kamojang dan Taman Wisata Alam Kamojang, Kabupaten Bandung, Provinsi Jawa Barat. Lokasi yang terkena dampak langsung berada di sekitar sumur produksi atau pembangkit listrik tenaga panas bumi (30 sampel) sedangkan lokasi yang tidak terdampak langsung adalah dengan jarak 3.000 m sampai 9.000 m dari fasilitas tersebut (42 sampel). Pengumpulan data dilakukan selama dua musim; musim kemarau dan penghujan (2015-2016). Kami mengumpulkan data komunitas burung dengan metode point count yang ditempatkan secara sistematis di setiap lokasi. Kami menemukan 124 jenis burung di CA/TWA Kamojang dan 90 jenis (1560 individu) burung pada titik contoh. Jumlah jenis dan jumlah individu burung di lokasi TL lebih besar dibanding lokasi DL. (lokasi DL (65 jenis; 525 individu) dan lokasi TL (72 jenis; 1035 individu). Terdapat perbedaan respon antara komunitas burung di lokasi DL dan TL yang ditunjukkan dengan perbedaan rata-rata jumlah jenis dan jumlah individu tiap titik contoh. Rata-rata jumlah jenis dan jumlah individu burung tiap titik contoh pada lokasi TL lebih besar dibandingkan lokasi DL. Kawasan CA/TWA Kamojang mempunyai dari 7 macam guild burung yaitu : insektivora, frugivora, granivora, nektarivora, karnivora, piscivora dan omnivora.Hasil uji signifikansi terhadap jumlah jenis dan jumlah individu setiap guild menunjukkan tidak adanya perbedaan nyata antara lokasi DL dan TL, namun pada lokasi DL burung-burung yang ditemukan merupakan burung yang umum ditemukan (generalis) dan burung yang ditemukan di lokasi TL sebagian besar merupakan burung spesialis. Hal ini membuktikan bahwa lokasi TL memiliki kondisi lingkungan yang lebih baik atau relatif tidak terganggu.